Bureaucratic Innovation and Public Service Delivery: Breaking Through Administrative Barriers in the Digital Era - Syafaruddin Syafaruddin; Andi Riska Andreani Syafaruddin; Nurasia Natsir (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Bureaucracies worldwide face increasing pressure to innovate due to rising citizen expectations, technological disruption, and fiscal constraints. The digital era offers significant opportunities to transform public service delivery by overcoming traditional administrative barriers. This study employs a multiple case study design, analyzing 18 innovative public service initiatives in Indonesia recognized for service innovation. Data were collected through document analysis, semi-structured interviews, and direct observations. Using Innovation Diffusion Theory and Institutional Theory, the study examines innovation adoption, implementation, and sustainability. The findings show that successful bureaucratic innovations share six key characteristics: strong leadership, citizen-centric design, effective use of digital technologies, incremental implementation, institutionalization through regulations, and external partnerships. However, major barriers include rigid regulations, risk-averse organizational culture, fragmented authority, limited resources, inadequate digital infrastructure, and political influences. Digital technology plays a crucial enabling role, yet it must be supported by organizational change, capacity building, and cultural transformation. This study provides policy recommendations to support regulatory reform, strengthen innovation systems, and foster innovation-friendly public sector environments.